2015
DOI: 10.1016/j.ijheatmasstransfer.2014.08.083
|View full text |Cite
|
Sign up to set email alerts
|

On the critical thickness and wavelength of a condensing thin liquid film in a binary vapor mixture system

Abstract: We study the linear stability of a condensing thin liquid film of a binary vapor mixture by solving directly the bulk equations of the gas phase. The boundary layer of a finite thickness is introduced above the liquid film, within which the variables are disturbed. The dynamics of the liquid film is described by the long-wave equation. The neutral stability condition predicts the existence of a critical thickness below which a flat film is stable due to the mass gain effect. However, if we consider the thicken… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Sc = µ ρD (27) where c p is the specific heat at constant pressure, J•kg −1 •K −1 ; and µ is the dynamic viscosity, Pa•s. Since the conduction heat transfer is much smaller than the condensation heat transfer in the vapor diffusion layer, the energy Equation (24) can be neglected.…”
Section: Governing Equationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sc = µ ρD (27) where c p is the specific heat at constant pressure, J•kg −1 •K −1 ; and µ is the dynamic viscosity, Pa•s. Since the conduction heat transfer is much smaller than the condensation heat transfer in the vapor diffusion layer, the energy Equation (24) can be neglected.…”
Section: Governing Equationsmentioning
confidence: 99%
“…By applying long-wave approximation, Kanatani [26] studied the instability of the condensate film in a binary vapor mixture system and found that the effect of temperature on condensation transfer coefficient could not be neglected in the condensation of a water-ethanol system. Later, by employing the asymptotic analysis for large wavenumbers, Kanatani [27,28] numerically calculated the critical thickness, the mean mass flux, and wavelength for the water-ethanol system. Li et al [29] proposed a semi-theoretical model to predict the condensation heat transfer characteristic of ethanol-water mixtures.…”
Section: Introductionmentioning
confidence: 99%